Pengaruh Pemasaran Sensorik terhadap Niat Beli Ulang Konsumen Mako Cake and Bakery Panakkukang Square dengan Kepuasan sebagai Variabel Mediasi - Arkam Susilo; Anwar Anwar; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Rahmat Riwayat Abadi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine the effect of sensory marketing on customer repurchase intention, with customer satisfaction as a mediating variable at Mako Cake and Bakery Panakkukang Square. The main focus of this research is to understand how sensory marketing which includes elements as sight, hearing, smell, taste, and touch influences customer repurchase intention and how customer satisfaction plays a role as a mediator. This research uses a quantitative approach. Data were collected through a questionnaire distributed to 220 respondents, who are customers of MAKO Cake and Bakery Panakkukang Square. The method used in this study is Structural Equation Modeling (SEM) supported by Smart PLS 4.0 software. The data analysis process includes validity testing, reliability testing, and structural model testing. The results of the study show that: (1) Sensory Marketing has a positive and significant effect on repurchase intention of MAKO Cake and Bakery Panakkukang Square customers, (2) Sensory Marketing has a positive and significant effect on customer satisfaction at MAKO Cake and Bakery Panakkukang Square, (3) Customer satisfaction has a positive and significant effect on repurchase intention at MAKO Cake and Bakery Panakkukang Square, (4) Customer satisfaction has a positive and significant partial mediating effect on the relationship between sensory marketing and repurchase intention at MAKO Cake and Bakery Panakkukang Square.